2016
DOI: 10.7863/ultra.15.11059
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Peripheral Intravenous Catheter Training Results in Physician‐Level Success for Emergency Department Technicians

Abstract: With brief but comprehensive training, ED technicians can successfully obtain US-guided peripheral IV catheter access in patients with difficult IV access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 25 publications
3
82
0
Order By: Relevance
“…While the traditional method of vein palpation for cannulation is effective in the majority of patients, those with difficult vascular access (DVA) present a daily challenge to hospital staff. There are approximately 150 million IVs placed annually in the US [1], with 10-30% of Emergency Department (ED) patients classified as DVA [2]. In these patients, placement of an ultrasound (US) guided IV catheter is a viable and safe option, and has been shown to increase patient satisfaction [3].…”
Section: Introductionmentioning
confidence: 99%
“…While the traditional method of vein palpation for cannulation is effective in the majority of patients, those with difficult vascular access (DVA) present a daily challenge to hospital staff. There are approximately 150 million IVs placed annually in the US [1], with 10-30% of Emergency Department (ED) patients classified as DVA [2]. In these patients, placement of an ultrasound (US) guided IV catheter is a viable and safe option, and has been shown to increase patient satisfaction [3].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, suggests that POCUS promotes indirect cost savings (eg, reducing patient discomfort, saving time for patients and providers), especially in the context of procedures. At least 1 study from 2016 has drawn a parallel conclusion about indirect savings: ultrasound‐trained ED technicians were able to place intravenous (IV) lines with ultrasound guidance in fewer attempts (1.15 attempts, on average), in patients classified as difficult by access criteria, than published studies indicated to be the case for nontrained technicians (1.27–1.70 attempts) . Furthermore, this 2016 study showed that ultrasound‐trained technicians placing IV lines with ultrasound guidance reached first‐attempt success rates of 97%, nearly equivalent to published success rates for nurses and physicians .…”
Section: Discussionmentioning
confidence: 75%
“…At least 1 study from 2016 has drawn a parallel conclusion about indirect savings: ultrasound-trained ED technicians were able to place intravenous (IV) lines with ultrasound guidance in fewer attempts (1.15 attempts, on average), in patients classified as difficult by access criteria, than published studies indicated to be the case for nontrained technicians (1.27-1.70 attempts). 29 Furthermore, this 2016 study showed that ultrasound-trained technicians placing IV lines with ultrasound guidance reached first-attempt success rates of 97%, nearly equivalent to published success rates for nurses and physicians. 29 Although the present work does not specifically assess the indirect cost savings associated with ED physicians using POCUS for IV access, it does suggest that POCUS can allow technicians to reach physician-level proficiency at IV placements, sparing patients discomfort and hastening their time in the ED, and facilitating providers' treatment and throughput of patients.…”
Section: Indirect Cost and Patient Carementioning
confidence: 83%
See 1 more Smart Citation
“…Only one randomised study conducted in selected trained emergency nurses has demonstrated that, in anticipated difficult intravenous access patients, an ultrasound-guided method was associated with a higher success rate compared with the LM. Vascular access in ICU is, on the other hand, a specific condition which cannot be compared with the emergency department setting [5][6][7]. B-ultrasound guided indwelling needle puncture of external jugular vein achieved satisfactory results in establishing fast venous access for critical patients with microcirculation failure before setting up CVC access from September 2018 to June 2019.…”
Section: Introductionmentioning
confidence: 99%